2013
DOI: 10.1371/journal.pone.0084159
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation Decreases Pain Threshold in Humans In Vivo

Abstract: BackgroundHyperalgesia is a well recognized hallmark of disease. Pro-inflammatory cytokines have been suggested to be mainly responsible, but human data are scarce. Changes in pain threshold during systemic inflammation evoked by human endotoxemia, were evaluated with three quantitative sensory testing methods. Methods and ResultsPressure pain thresholds, electrical pain thresholds and tolerance to the cold pressor test were measured before and 2 hours after the intravenous administration of 2 ng/kg purified E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 27 publications
9
65
0
Order By: Relevance
“…In models controlling for all other measures of inflammation, the relationships between TLR-4 inflammatory responses and pain scales were not attenuated; this provides strong evidence that TLR-4 mediated inflammation specifically plays a critical role in IC/BPS pain symptoms. These findings may be related to recent work demonstrating that experimental induced endotoxemia via LPS administration reduces pain thresholds in healthy subjects [8]. …”
Section: Discussionsupporting
confidence: 74%
“…In models controlling for all other measures of inflammation, the relationships between TLR-4 inflammatory responses and pain scales were not attenuated; this provides strong evidence that TLR-4 mediated inflammation specifically plays a critical role in IC/BPS pain symptoms. These findings may be related to recent work demonstrating that experimental induced endotoxemia via LPS administration reduces pain thresholds in healthy subjects [8]. …”
Section: Discussionsupporting
confidence: 74%
“…A recent meta-analysis showed that sleep disturbance is associated with increase in markers of systemic inflammation [99]. Interestingly, systemic inflammation resulted in lowering pain threshold [100]. Additionally, the tumor necrosis factor (TNF) system [101] as well as the hypothalamic-pituitary-adrenal-axis [102] are influenced by sleep and pain.…”
Section: Discussionmentioning
confidence: 99%
“…During systemic inflammation after administration of endotoxin to volunteers, widespread pressure hypersensitivity develops [102]. Furthermore, low-dose endotoxin potentiates capsaicin-induced pain and hyperalgesia/allodynia [103].…”
Section: Extrasegmental Widespread Sensitizationmentioning
confidence: 99%